(untitled) (Revista Argentina de Cirugía, 2026)
Caroli’s disease is a congenital disease presenting with jaundice, choluria and white-colored stool. Diagnosis is often difficult because it is a rare condition and patients report several recurrent similar episodes before a diagnosis is made. Suspicion is important for early treatment and avoidance of interventional procedures that may increase the risk of infection. We report the case of a 74-year-old woman with unilateral Caroli’s disease who presented with jaundice, choluria and white-colored stool. The patient underwent left liver resection with construction of a right Roux-en-Y cholangiojejunostomy. Resection of the abnormal ducts has been shown to prevent new dilations in the regenerated liver. This explains the excellent results obtained with this approach in the long-term.